Efficacy and safety of complement inhibitors in patients with geographic atrophy associated with age-related macular degeneration: a network meta-analysis of randomized controlled trials - Huan Wang; Jiaqi Zheng; Qing Zhang; Zhongping Tian; Yuhang Sun; Tianyi Zhu; Yanlong Bi; Yanlong Bi; Li Zhang; Li Zhang (Frontiers Media S.A., 2024)
ImportanceClinical trials in recent years have shown significant effectiveness of complement inhibitors for geographic atrophy (GA) treatment. Two complement inhibitor drugs have been approved by the Food and Drug Administration (FDA).Objectiveto compare and rank the different complement inhibitors in the treatment of GA secondary to age-related macular degeneration (AMD).Data sourcesA systematic literature search was conducted in the Cochrane Central, Web of Science Core Collection, PubMed, LWW Medical Journals, ClinicalTrials.gov, and WHO ICTRP from inception to October 2023.Study selectionAll randomized clinical trials evaluating the effectiveness of complement inhibitors in patients diagnosed with secondary GA in AMD were identified.Data extraction and synthesisThis study followed Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) network meta-analysis Checklist of Items and the Cochrane Risk of Bias Assessment Tool for assessing the study quality. Multiple authors independently coded all titles and abstracts, reviewed full-text articles against the inclusion and exclusion criteria, and resolved all discrepancies by consensus. Random-effects network meta-analyses were applied. Bayesian network meta-analysis was performed using the BUGSnet package in R (4.2.0).Main outcomes and measuresThe primary efficacy outcome was the change in GA lesion size (mm2) from baseline to month 12. The secondary efficacy outcome was the mean change in best-corrected visual acuity (BCVA) from baseline to month 12. Safety outcome measures included the number of subjects with serious adverse events (SAEs) and macular neovascularization (MNV).ResultsTen randomized controlled trials including 4,405 participants and five complement inhibitors were identified. Comparison with sham and SUCRA analysis showed that avacincaptad pegol 2 mg (MD: −0.58, 95% CrI: −0.97 to −0.18, SUCRA: 93.55), pegcetacoplan monthly (MD: −0.38, 95% CrI: −0.57 to −0.20, SUCRA: 81.37), and pegcetacoplan every other month (MD: −0.30, 95% CrI: −0.49 to −0.11, SUCRA: 70.16) have significant changes in GA lesion reduction. No treatments showed significant changes in BCVA and SAE compared with sham. Pegcetacoplan monthly (OR: 4.30, 95% CrI: 1.48-16.72) increased the risk of MNV. Avacincaptad pegol 2 mg demonstrated favorable outcomes in terms of SAE and MNV.Conclusion and relevanceAvacincaptad pegol 2 mg is the most effective complement inhibitor with better safety for the treatment of GA secondary to AMD.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022351515, Identifier PROSPERO CRD42022351515.